If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + c = 13 Solving 3 + c = 13 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + c = 13 + -3 Combine like terms: 3 + -3 = 0 0 + c = 13 + -3 c = 13 + -3 Combine like terms: 13 + -3 = 10 c = 10 Simplifying c = 10
| 4/5÷8/9= | | 3a-4=-9 | | 4/5x-4=12 | | x^2y-3xy^2= | | -8y+24=-5(y-6) | | 3(2-b)=36 | | 5-x/6=1 | | 12-2x/48=3x-6/72 | | 120=-20x | | 2t+6=6t-10 | | 7x+8-4x=10 | | x^3+3x^2-25x=75 | | .08-.12(x-4)=.03(x-5) | | x-5+x+x+2=45 | | 7(2+2n)-7=-91 | | 7-5y=102 | | 3(-3)-y=7 | | 3/(2x-9)=8-3x | | 8-(w+7)=.5 | | (4/5)*5 | | 8(y-1)=6(2y-6) | | -3(v-4)=12-3v | | 2v+17=23 | | 4x-5=5x+21 | | (3x^4)-(19x^2)-40=0 | | 3(8-3a)-5=91 | | 9(z-3)=-12z | | 14=-2(3-m) | | 4x-1x(9-3x)=8x-1 | | 2/5x3/4= | | 7x-7x=3 | | 2n+1=63 |